2016
DOI: 10.1088/1475-7516/2016/11/027
|View full text |Cite
|
Sign up to set email alerts
|

Supermassive dark-matter Q-balls in galactic centers?

Abstract: Though widely accepted, it is not proven that supermassive compact objects (SMCOs) residing in galactic centers are black holes. In particular, the Milky Way's SMCO can be a giant nontopological soliton, Q-ball, made of a scalar field: this fits perfectly all observational data. Similar but tiny Q-balls produced in the early Universe may constitute, partly or fully, the dark matter. This picture explains in a natural way, why our SMCO has very low accretion rate and why the observed angular size of the corresp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 106 publications
(158 reference statements)
0
11
0
Order By: Relevance
“…Very recently there was a strong interest for astrophysical objects presenting scalar hairs, see for example [23], [24], [25], [26]. This type of research motivate the study of the possible hair structure occurring around compact gravitating objects.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently there was a strong interest for astrophysical objects presenting scalar hairs, see for example [23], [24], [25], [26]. This type of research motivate the study of the possible hair structure occurring around compact gravitating objects.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]. Observing such Qballs travelling in the Universe would have striking consequences: their discovery would support supersymmetric extensions of the Standard Model [4,5], Q-balls could have participated in baryogenesis [6] and formation of boson stars [7], and the dark matter [5,[8][9][10] and supermassive compact objects in galaxy centres [11] may consist of Q-balls. Nevertheless, unambiguous experimental evidence on Q-balls has so far not been found in cosmology or in high-energy physics.…”
Section: Introductionmentioning
confidence: 99%
“…1 During the years of studies, they found numerous applications in different branches of modern physics. Q-balls are predicted in models of physics beyond the Standard Model [6], and were applied to different problems in astrophysics and cosmology (baryogenesis [7], phase transitions in the Early Universe [8], dark matter [9], alternative to black holes [10]). Beside that, the existence of Q-balls is discussed, e.g., in condensed matter physics [11].…”
Section: Introductionmentioning
confidence: 99%